Wykonywanie funkcji publicznych przez duchownego w procedurze zawierania małżeństwa cywilnego w formie wyznaniowej - Tunia, Anna (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: The subject of the following article is a presentation of the scope of public functions which a priest accomplishes in the procedure of contracting the civil marriage in the confessional form. First of all, the article points at the basis of entitlement to perform those duties and the nature of activities the priest is dealing with. It was elucidated that the priest is not a public official but in the course of discussed proces he executes the tasks following the extent of public administration.